Analysis of Seismic Attributes and Band-Limited Inversion for Re-Determining The Hydrocarbon Prospect Zone in Data F3 Netherland - Ayi Syaeful Bahri; Pegri Rohmat Aripin; Adib Banuboro; Alfaq Abdillah Robi (IPTEK Journal of Proceedings Series, 2017)
The aim of this study was to determine the prospect zone of hydrocarbons in Dutch F3 field by utilizing seismic attribute analysis and band-limited inversion. The research data used comes from open source that can be downloaded at opendtect.com. Data processing uses Humpson Russel Software (HRS) to perform well to seismic tie and inversion. Interactive Petrophysics Software for well data analysis, crossplot and potential hydrocarbon estimates, and Petrel Software for well tie load data and seismic attribute analysis. Re-determination of the hydrocarbon prospecting zone includes data selection, log and seismic data processing, horizon and fault interpretation, time structure map and depth structure map, and seismic attribute analysis. From each of these stages will be integrated analyzed on the results of workmanship and geological interpretation of the sustainability of the top reservoir target. Based on the results of clay volume analysis using IP software with Gamma Ray as input parameters, it can be seen that the well that has the biggest prospect is the well F02-1 (774-919 meters) and F06-1 (770-825 meters). This is because the volume of sand in the prospect zone of both wells is larger than the other two wells. The hydrocarbon target depth is in the time to 250 to 500 second (time map structure) or 550 meters (depth conversion) with reservoir lithology in the form of shaly sand with gas fluid as filler.